Hybrid nitrogen-doped graphene-supported MoS2 nanosheets with synergistic effect for high-performance supercapacitor electrodes - Ravindran, Nithyialakshmi; Sookhakian, M.; Tong, Goh Boon; Yatimah, Alias (SpringerLink, 2025)
Efficient supercapacitor electrodes have been developed from a nitrogen-doped graphene-molybdenum disulfide composite (NG/MoS2) with varying NG concentrations fabricated on nickel foil electrodes. The successful synthesis of NG and MoS2 nanosheets was confirmed through Raman spectroscopy, X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). At the same time, the morphology was studied using FESEM and TEM. The influence of varying NG concentrations on the electrochemical properties of the MoS2 nanosheets was investigated. The composite containing 1% NG achieved a maximum specific capacitance of 897.6 F/g at a current density of 1 A g−1 , surpassing the electrochemical performance of pristine MoS2, which had a capacitance of 291.1 F/g under the same conditions. This improvement arises from the synergistic interaction between superior catalytic properties found in the MoS2 nanosheets and conductivity provided by the addition of NG, which was confirmed through electrochemical impedance spectroscopy (EIS). In conclusion, this work may offer a way to fabricate supercapacitor electrodes with improved specific capacitance and energy density for energy storage.